Studi Komparasi Model Pembelajaran Problem Solving dengan Group Investigtion disertai Concept Map terhadap Hasil Belajar Siswa Kelas X SMA N 8 Surakarta - Yayuk Widyastuti; Harlita Harlita; Baskoro Adi Prayitno (BIO-PEDAGOGI, 2014)
This research is motivated by teachers who often conveying all course materials so that students become less active because they only served to listen and rarely given the opportunity to ask. A less active role in the learning resulted in student’s understanding of the material tends to show and the student’s achievements at the cognitive, affective, and psychomotor less than optimal. This research is aimed to determine differences of student’s achievements between Problem solving-Concept maps with Group Investigation-Concept map. This research is Quasy Experimental use Post-test Only with Nonequivalent Group Design. All of tenth grade students of SMAN 8 Surakarta are sample population. The sampling technique in this study was cluster sampling with a sample size of 53 students. Data collection using tests and non-test method. Test methods include multiple choice questions while the non-test includes observation and documentation. Based on the t-test, cognitive showed that Sig. (0,755) > 0,05, affective showed that Sig. (0,009) < 0,05, and psychomotor showed that Sig. (0,000) < 0,005. The conclusion of this research is didn’t show any difference in student’s achievements in the cognitive between experimental class 1 and experimental class 2 but showed differences in affective and psychomotor domains. Key Words: Problem Solving Learning Model, Group Investigation Learning Model, Concept Map, Student’s Achievements